Comparison of the nutrient composition of sludge under aerobic and anaerobic mineralization from African catfish, Clarias gariepinus (Actinopterygii: Siluriformes: Clariidae), reared in an intensive recirculating aquaculture system - Rizza Mae Guyapale; Cleresa Dionela; Fredson Huervana (Acta Ichthyologica et Piscatoria)
One of the major challenges in an intensive recirculating aquaculture system (RAS) is the sustainable management of fish sludge. The sludge contains a significant amount of nutrients that can be utilized by hydroponically grown crops in an integrated system called aquaponics. While this system has promising results, techniques to maximize nutrient recovery still need to be developed. African catfish, Clarias gariepinus (Burchell, 1822), can be stocked at very high densities, therefore it produces a substantial amount of sludge. In this study, sludge from African catfish RAS was subjected to different mineralization treatments (T1: anaerobic, T2: aerobic, and T3: aerobic with carbon addition) for nutrient recovery. The supernatant in T3 after mineralization had a statistically significant difference (P > 0.05) in their concentrations of N (2700 mg ∙ L–1), P (100 mg ∙ L–1), K (720 mg ∙ L–1), Ca (12 115.6 mg ∙ L–1), and Mg (3391.9 mg ∙ L–1) after 15 days, among the other mineralization methods and untreated sludge. It was then followed by the nutrient recovery performance of T2 and lastly, T1. Moreover, the low pH and warm temperature were observed to improve the solubilization of the nutrients, resulting in a higher nutrient recovery in T3. Hence, among the three mineralization treatments, T3 had the most potential to recover maximum nutrients from African catfish sludge to be used as organic fertilizer for hydroponically grown crops.